Microfabrics in eolian sandstones of the De La Cuesta Formation (Permian), Sierra de Narváez, Catamarca Province, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
In this paper a study of microfabrics occurring in eolian Permian sandstones of the De La Cuesta Formation (Catamarca Province, northwest Argentina) is presented (Fig. 1). The middle part of the De La Cuesta Formation comprises thick and well exposed eolian sandstones, which were deposited in an erg environment during an arid Permian phase recognized in different parts of South America (Spalletti et al., 2011, Fig. 2). Following the scheme proposed by Spalletti et al. (2011) samples were collected from the following sedimentary facies: 1) cross-bedded fine-grained sandstones interpreted as crescent dunes, 2) wedge-shaped cross-bedded sandstones corresponding to longitudinal (seif) dunes, 3) horizontal-laminated or low-angle crosslaminated sandstones, in some cases showing inverse-grading, which would have been deposited in interdune and extradune (eolian sand-sheet) areas, and 4) fine- to very fine-grained sandstones formed in dry and wet interdunes (Figs. 2 and 3). On the basis of texture (grain size, sorting and asymmetry) and microstructures, six microfabrics were recognized (Table 1). Microfabric 1 comprises grainflow-foreset laminae found in large-scale cross-bedded sandstones; this type of microfabric is composed of medium-grained sandstones (less commonly coarse-grained sandstones) with mean values between 300 ? y 460 ? (Table 1). The sandstones are unimodal, moderately well sorted and the grain size distribution is slightly asymmetric (Fig. 5); they are composed of medium-grained sand (55%), fine-grained sand (21%) and coarse-grained sand (24%). Coarse-grained silt is almost entirely absent, and the intergranular space varies from 25% to 27%. This microfabric forms inclined laminae, 3 to 5 cm thick, commonly decreasing in thickness towards the base of the set. Microfabric 2 occurs closely associated with microfabric 1 forming large-scale cross-bedded sets. It corresponds to grainfall deposits and is mainly formed by fine-grained and less frequently by very finegrained sandstones (Table 1 and Fig. 5). Microfabric 2 is mainly composed of fine-grained sand (60%), very fine-grained sand (31%), medium-grained sand (7%) and coarse-grained silt (2%). The laminae are tabular, massive and their thickness range from 0.5 to 4 cm; the intergranular space is lower than microfabric 1 (17%-20%, Table 1 and Fig. 6). Microfabric 3 is made up by laminae of inverse graded sandstones, whose thickness vary from 10 mm to 30 mm, being the intergranular space between 10% and 15% (Figs. 5, 6 and 8). The particle size distributions are unimodal, moderately sorted with mean values in medium-grained sand (250 ? y 300 ?, Fig. 5). In almost all cases, the medium-grained sand prevails (42%), followed by fine-grained sand (38%), coarse-grained sand (13%) and very fine-grained sand (6%); coarse-grained silt is below 1% (Table 1, Fig. 6). This microfabric is interpreted as originated by the migration of eolian ripples that carried an appreciable amount of coarse- and medium-grained sand transported by creeping. Microfabric 4 is characterized by fine-grained unimodal, moderately well sorted sandstones with a slightly asymmetric distribution (Figs 5, 6 and 9). The average grain-size distribution is: fine-grained sand (50%), very fine-grained sand (28%), mediumgrained sand (20%) and coarse-grained sand (1.5%); the percentage of coarse-grained silt ranges from 1% to 8% (Table 1). Microfabric 4 is quite similar to microfabric 3, but it differs in the lack of graded lamination and in a higher proportion of fine-grained sand. As in the case of microfabric 3, this microfabric was probably formed by the migration of eolian ripples, but lacking enough amount of coarse- and medium-grained sand to promote graded structures. Massive very fine-grained and fine-grained sandstones showing adhesion ripples, bioturbation and centimeter-scale deformational structures, correspond to the microfabric 5. This microfabric dominates in dry interdune and extradune deposits. Sandstones are characterized by abundant carbonate (calcite) cement and high intergranular space (28%- 30%). The particle size distribution is unimodal, moderately sorted, and dominated by very finegrained sand (44%) and fine-grained sand (39%), followed by discrete proportions of medium-grained sand (9%) and coarse-grained silt (7%); in all cases the amount of coarse-grained sand is lower than 1% (Table 1 and Fig. 6). Microfabric 6 exhibits the smallest grain-sizes and predominates in wet interdune and extradune deposits. It consists of well sorted, very fine-grained sand (media between 95 and 80 ?). The dominant very fine-grained sand population (72%) is accompanied by coarse-grained silt (17%) and fine-grained sand (10%, Table 1 and Fig. 6). The beds are massive, horizontally laminated or exhibit wavy lamination originated by post-depositional compaction. The mentioned microfabrics appear not randomly distributed, but they form specific associations among the different types of the dune, interdune and extradune deposits (Fig. 10). In the case of dune sandstones, the foresets of large-scale crossbedded units are mainly composed of alternated laminae of microfabrics 1 and 2, which represent the alternation of grainflow and grainfall processes. Less frequently, foresets comprise microfabrics 3 and 4, suggesting the development of lamination produced by migration of ripples on leeward side of dunes. A particular type of dune cross-bedded sets result from the stacking of laminae formed by microfabric 2, pointing out that grainfall of fine- and very fine-grained sand occurs without grainflow events or significant migration of ripples. In such circumstances, cross-laminated sets form pinstripe lamination, suggesting the development of lowangle leeward dune faces. Dry interdunes are chiefly composed of microfabrics 3 and 4, which show that ripple migration is the main mechanism of transport and deposition in this setting; scarce intercalations of microfabric 5 are interpreted as remobilized sand accumulations related to deflation and/or fluvial floods in interdune areas (Fig. 10). Deposits of wet interdunes comprise microfabrics 5 and 6 with minor contributions of microfabrics 3 and 4. Extradunes are formed by thick intervals (tens of meters) of horizontal laminated or low-angle crosslaminated sandstones. In these deposits microfabric analysis allows discriminating between dry and wet extradunes, since the former are characterized by microfabrics 3 and 4, whereas the second are essentially composed of microfabrics 5 and 6. Microfabric studies allow not only obtaining a more complete and precise information on the mechanism of transport and deposition in the eolian system, but also interpreting changes in the petrophysical features of the sandstones (permeability, porosity). Additionally, microfabric analysis can be employed as a useful tool in the description and interpretation of core wells.
Keywords: Clastic microfabric; eolian; Permian.